Supplementary notes on vowel lengthening in Danish - Fischer-Jørgensen, Eli (Annual Report of the Institute of Phonetics University of Copenhagen, 1983)
The recordings which formed the basis of Fischer-Jørgensen "Segmental duration of Danish words in dependency on higher level phonological units", ARIPUC 16, 1982, were supplemented by a number of new recordings containing mostly actual disyllables (i.e. words without apocope). The four West Jutlandish speakers read a supplementary list, and recordings were made of a number of new informants: seven dialect speakers from East Jutland, five from North Zealand, and two younger Copenhagen informants. It turned out that both West- and East Jutlandish speakers have vowel lengthening in actual disyllables but not in apocopated words (the same was true of the North Zealandish speakers who had apocope). There is thus more lengthening in the dialects than assumed in my 1982 report. Very conspicuous lengthenings were found in three North Zealandish coastal dialects, but somewhat less lengthening than expected in the speech of the two Copenhagen informants. The rejection of the hypothesis of a connection with apocope or with a special pitch contour was confirmed by the new recordings. The assumption of a connection with the weakness of the following consonant is upheld.